2018
DOI: 10.1002/dmrr.3025
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive changes in pancreas post Roux‐en‐Y gastric bypass induced weight loss

Abstract: Following RYGB, pancreatic volume and steatosis adaptively decreased to "normal" levels with accompanying improvement in glucose homeostasis. Moreover, obesity-driven beta-cell expansion seems to be reversible; however, future studies must define a method to more accurately estimate functional beta-cell mass to increase our understanding of glucose homeostasis after RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In our model, we did not find differences in insulin staining in b-cells in HFD rats and could not confirm the hypothesis discussed in recent mice models of diet-induced obesity 32 . However, as in the literature, we found an increase of the oral glucose tolerance test and insulin secretion after bariatric surgery 33 , 34 . Interestingly, we demonstrated that in our model, abnormal pancreatic features were detected not only in endocrine, but also in the exocrine pancreas, mainly observed beside HHF lesions, consisting in acinar-ductal metaplasia with inflammation, fibrosis, activation of stellate cells and iron deposits.…”
Section: Discussionsupporting
confidence: 84%
“…In our model, we did not find differences in insulin staining in b-cells in HFD rats and could not confirm the hypothesis discussed in recent mice models of diet-induced obesity 32 . However, as in the literature, we found an increase of the oral glucose tolerance test and insulin secretion after bariatric surgery 33 , 34 . Interestingly, we demonstrated that in our model, abnormal pancreatic features were detected not only in endocrine, but also in the exocrine pancreas, mainly observed beside HHF lesions, consisting in acinar-ductal metaplasia with inflammation, fibrosis, activation of stellate cells and iron deposits.…”
Section: Discussionsupporting
confidence: 84%
“…Knockout of hsa-miR-375 in a mouse model induced a hyperglycemic phenotype with reduced beta cell mass [37]. The increased level of circulating hsa-miR-375 might therefore indicate an amelioration of beta cell function or changes in beta cell mass as indicated previously [14].…”
Section: Discussionmentioning
confidence: 53%
“…When analyzing the pancreas in obesity, pancreatic fat accumulation is thought to accompany beta cell failure at least in animal models [13]. Recent data described a normalization of pancreatic volume and steatosis in morbidly obese patients following Roux-en-Y gastric bypass (RYGB) surgery [14]. Under normal physiologic conditions, insulin biosynthesis is a multi-step process beginning with a pre-prohormone which is converted in the rough endoplasmatic reticulum to proinsulin within beta cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the 96 . Since then, whereas one study confirmed this first finding 97 , others observed no change in pancreatic β-cell mass 98,99 post-BS. These diverging results might originate from the difficulty in directly assessing pancreatic tissue in humans.…”
Section: Changes In Hormones and Beta Cell Functionmentioning
confidence: 91%
“…These diverging results might originate from the difficulty in directly assessing pancreatic tissue in humans. Some groups have thus evaluated β-cell mass or function using tomography or magnetic resonance imaging to assess pancreatic triglyceride content 100 coupled with functional exploration (Cpeptide production and insulin sensibility) 99 . Rather than increase observed previously, a decrease in pancreatic β-cell mass was shown due to the reduction in pancreatic steatosis and decreased pancreatic insulin content, a phenomenon suggested to be linked to pancreas adaptation following weight loss.…”
Section: Changes In Hormones and Beta Cell Functionmentioning
confidence: 99%